Laser technology - Huamin, Cao; Lan, Xinju (CRC Press/Taylor & Francis, 2010)
As different laser technologies continue to make it possible to change laser parameters and improve beam quality and performance, a multidisciplinary theoretical knowledge and grasp of cutting-edge technological developments also become increasingly important. The revised and updated Laser Technology, Second Edition reviews the principles and basic physical laws of lasers needed to learn from past developments and solve the many technical problems arising in this challenging field. The first edition of Laser Technology was classified by the Chi.